Impact of E-Learning Quality on Student Satisfaction During Covid-19 and Continuing Intentions to Use E-Learning Post Covid-19 - Setiawati, Anindya Prastiwi; Bhakti H, Frestina (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The COVID-19 pandemic has forced all educational institutions to adopt online learning, regardless of how ready they are for transformation. This study aims to investigate student perceptions of e-learning quality, student satisfaction, and intention to continue using online education. It is also found that students in some areas are not ready to adapt from face-to-face offline education to e-learning platforms, examining how the quality of e-learning affects student satisfaction and usage intentions will provide useful findings for policy makers and educators to improve e-learning effectiveness. Utilizing quantitative methods, this study uses an online survey questionnaire to test the suggested research hypotheses and test the proposed model. To analyze and test the data, AMOS 20.0 was used using SEM (structural equation modeling). Based on the results of testing the impact of e-learning quality on student satisfaction and sustainable use intentions among higher education students, several conclusions can be drawn. Increasing student satisfaction by improving the quality of e-learning has resulted in greater efficiency and effectiveness of student online learning performance and outcomes. There is a strong significant relationship between knowledge sharing, communication facilities, motivation and use, and acceptance of e-learning between instructors.